2005
DOI: 10.1093/ps/84.8.1314
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the spread of hatch and interaction with delayed feed access after hatch on broiler performance until seven days of age

Abstract: Delay in access to feed for 1-d-old chicks impairs posthatch growth. It is a standard practice that 1-d-old chicks are deprived of feed for about 48 h before they are placed on farms. During incubation, there is a spread of 24 to 48 h for late versus early hatching. As spread of hatch increases, number of chicks that are feed-deprived for a longer time before free access (IA) to feed and water increases. In this current study, we investigated the effects of time delay in feed access on chick juvenile relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
145
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(167 citation statements)
references
References 21 publications
16
145
2
4
Order By: Relevance
“…One assumption is that the chicks are similar in physiological status at hatch, giving a baseline with which to compare the results obtained at pulling. While this is true for most physiological parameters including BW, some organ weights and hormone levels (Careghi et al, 2005;van de Ven et al, 2013;Maatjens et al, 2014), other parameters do differ slightly, such as glucose levels and heart weight, making it more difficult to compare these to chicks at pulling. Numerous factors influence hatching time and chick quality, such as breeder age, genetic strain and egg storage conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One assumption is that the chicks are similar in physiological status at hatch, giving a baseline with which to compare the results obtained at pulling. While this is true for most physiological parameters including BW, some organ weights and hormone levels (Careghi et al, 2005;van de Ven et al, 2013;Maatjens et al, 2014), other parameters do differ slightly, such as glucose levels and heart weight, making it more difficult to compare these to chicks at pulling. Numerous factors influence hatching time and chick quality, such as breeder age, genetic strain and egg storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality day-old chicks ensure greater survivability and better growth potential during the early post-hatch stages (Christensen, 2009). There have been previous studies investigating the physiological status of chicks shortly after hatch and these show no difference in chick weights relative to the time of hatch (Careghi et al, 2005;van de Ven et al, 2013;Maatjens et al, 2014). However, there is no specific data to show how weight, chick quality or other physiological parameters at pulling are influenced by the precise duration of the holding period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longer egg storage duration results in a longer incubation time (Christensen et al, 2002). Thus, mixing eggs from different storage period affects the hatch spread, which is referred to 12 to 48 h of hatch window (Decuypere et al, 2001;Careghi et al, 2005). It was reported that 80% of the chicks from eggs stored for 3 days hatched before 490 h of incubation, whereas this number was obtained at 500 h of incubation for chicks from eggs stored for 18 days (Tona et al, 2003).…”
Section: Introductionmentioning
confidence: 99%